Analisis Penyebaran Air Tercemar Akibat Pembuangan Sampah Sembarangan - Harefa, Sesilia Viktoria (Jurnal Perikanan dan Kelautan, 2025)
Littering has become a major contributor to water pollution, especially in urban areas and watersheds. This article aims to analyse the spread of polluted water due to people's behaviour in disposing of waste, based on a review of recent literature. The method used is a literature study of various relevant national scientific journals for 2021-2025. The results showed that unmanaged household waste, plastic, and organic waste are the dominant factors in water pollution, which has an impact on the decline in the quality of aquatic ecosystems, public health, and social and economic damage. Integrated waste management, environmental education, and strict monitoring of community behaviour are needed as the main solutions.